ANALYSIS OF HERBACEOUS DIVERSITY IN FIRE AFFECTED AREAS OF BHORAMDEO WILDLIFE SANCTUARY, CHHATTISGARH - M. K. JHARIYA; P. R. ORAON (The Bioscan, 2012)
The present work aimed to study the impact of forest fire on herbaceous vegetation of Bhoramdeo Wildlife Sanctuary situated in Chhattisgarh. Four sites (High, medium, low and non-fire zone) were selected; in each of these sites pre-fire and post-fire observation were taken for measuring varying degree of disturbances. A total of 19 and 30 herbs species were recorded during pre-fire season and post-fire season, respectively. The total densities of herbs in pre-fire season were ranged from 112000 to 668000 ha-1, whereas during post-fire it varied from 230000 to 510000 ha-1. The herb layer showed higher density after post-fire in high and low fire zones, whereas decreased in medium fire zone due to the change in season (rainy), the density of herb layer also increased (40.03%) after post-fire in non-fire zone. The diversity indices in pre-fire season showed that Shannon index in different fire zones varied from 1.69 to 2.71, concentration of dominance (Cd) 0.20 to 0.36, species richness 0.33 to 0.67, equitability 1.05 to 1.33 and beta diversity 1.9 to 3.8, whereas during the post-fire season Shannon index and species richness values were increasing. The abundance to frequency ratio (A/F) indicated most of the species performed contagious pattern of distribution.